TCAD-Based Switching Performance Comparison of 3D Planar and Quasi-Planar Trench 3.3 kV SiC MOSFETs - Kansal, Mansha; Capasso, Giuseppe; Benjamin, Arne; Breglio, Giovanni; Lophitis, Neophytos; Irace, Andrea; Antoniou, Marina; Rahimo, Munaf; Maresca, Luca (My University, 2025)
A detailed numerical study of the dynamic behavior of 3D 3.3 kV SiC MOSFETs constructed with a conventional planar and Quasi-Planar Trench (QPT) design is conducted in this research. The motivation behind this research is to understand the concept and working of QPT, examining its merits and demerits. Static simulations were performed to obtain transfer and output characteristics, threshold voltage, and ON-Resistance (RON) - offering insights into the conduction behavior of the device. Further, the switching losses are examined and comparisons between the two structures is investigated with the help of advanced 3D TCAD simulations at both ambient and high temperature. Accordingly, the present study focuses on dynamic switching simulations, including Turn-ON, Turn-OFF, and Reverse Recovery conditions. The results of this research indicate that while the trench design can benefit from faster conduction and reduced RON, its reverse recovery and the tailing current during Turn-OFF significantly increases energy dissipation. The acquired insights throw light on the QPT architecture's capability to push the limits of high-voltage SiC based power devices.